Role Playing Method Decreases Communication Anxiety of Medical Students - Wulanyani, Ni Made Swasti; Sudarmaja, I Made; Surijah, Edwin Adrianta (Faculty of Psychology, Universitas Surabaya, 2008)
As a professional in public health services, a physician should be acquainted with commu- nication skills when interacting with all kinds of human character. An effective communication could be implemented to collect information as a prerequisite to make an accurate diagnosis and satisfy the patient as well. Anxiety haunting inexperienced students in facing real patients could block one’s real communication potential. The aim of this study was to assess whether the role playing method could decrease the anxiety scale of the subjects. Subjects (N = 70) were first semester medical students. The Communication Anxiety Scale were delivered before and after they conduct the role play. Data were analysed with t test. Results show a significant decline in anxiety scale (p < 0.001). The role playing method is able to decrease communication anxiety through simulation (training in a near-real situa- tion, stimulating imagination and verbal potentials). Sebagai profesional dalam bidang layanan kesehatan masyarakat, seorang dokter dituntut memiliki keterampilan komunikasi saat berhadapan dengan karakter manusia yang beragam. Komu- nikasi efektif dapat digunakan untuk menggali informasi demi tertegakkannya diagnosis yang akurat dan juga memuaskan pasien. Kecemasan yang timbul pada para mahasiswa yang belum berpenga- laman dapat menghambat kemampuan komunikasi yang sesungguhnya. Tujuan studi ini adalah me- nilai apakah metode bermain peran dapat menurunkan tingkat kecemasan para subjek. Subjek (N = 70) adalah mahasiswa semester 1 fakultas kedokteran. Skala Kecemasan Komunikasi disajikan se- belum dan setelah subjek melakukan permainan peran. Data dianalisis dengan t test. Hasil menun- jukkan bahwa tingkat kecemasan menurun secara signifikan (p < 0.001). Metode bermain peran telah berhasil menurunkan tingkat kecemasan komunikasi karena memberikan kesempatan berlatih dalam situasi yang mendekati kenyataan, merangsang imajinasi dan kemampuan verbal